Indonesia's State Policy in Resolving International Trade Barriers - Dodi Sugianto (Jurnal Syntax Admiration, 2023)
This journal article aims to review and analyze the policies that have been taken by the Indonesian government in resolving international trade barriers. We will look at how the policy is implemented, its impact on the Indonesian economy, as well as the challenges faced in the implementation process. This research uses qualitative methods with a library research approach. The qualitative method was chosen because this study aims to examine Indonesia's state policy in resolving international trade barriers thoroughly and in depth. Through this method, researchers can collect and analyze relevant secondary data from a variety of available sources, such as journal articles, books, official government documents, and international organization reports related to trade. The results of this study conclude that Indonesia's role in international trade disputes is very important in protecting national economic interests and encouraging dialogue and cooperation with its trading partner countries. Through participation in WTO mechanisms, bilateral diplomacy, and its role as a mediator, Indonesia seeks to resolve trade disputes in a manner that is fair and beneficial to all parties involved.